Examining the Ability of Aerobic Halophilic Heterotrophic Microbial Consortia to Replace Ca by Mg in Different CaCO3 Precursors - Alibrahim, Ammar; Dittrich, Maria (Frontiers in Microbiology, 2022)
Recent laboratory experiments have exhibited microbes as promising agents in solving the perplexing origin of ancient dolomite by demonstrating microbial capability to mediate dolomite nucleation and growth. However, dolomite crystals from laboratory experiments have shown irrelevant characteristics to ancient dolomite from mineralogical and petrological perspectives. A major irrelevant characteristic is that ancient dolomite was assumed to be formed after the replacement of Ca by Mg in precursor CaCO3 in a process known as diagenesis, which contrasts with the primary precipitation process observed in laboratory culturing experiments. Considering dolomite microbial experiments, one can imply the involvement of microbes in the formation of ancient dolomite as microbes have shown the ability to overcome the dolomite kinetic barrier. Despite that fact, the ability of microbes in mediating dolomite diagenesis has not been investigated. In this study, microbes were applied to mediate replacement of Ca by Mg in different CaCO3 precursors. The microbial replacement experiments were based on the enrichment of aerobic halophilic heterotrophic microbial consortia sampled from sediments collected from Al-Subiya sabkha in Kuwait. Two experiments were performed in saturated media at 35 oC for 14 and 30 days simulating the conditions of microbial dolomite experiments. The change in minerology was examined via powder XRD and the change in texture and compositional microstructures was examined using SEM-EDS. The effect of microbes on the alteration of CaCO3 precursors was studied by comparing biotic experimentations with abiotic controls. The biotic samples were shown to result in the favourable conditions for dolomite formation including an increase in pH and alkalinity, but no changes were observed in mineralogy or compositional microstructure of CaCO3 precursors. Our results suggest the inability of aerobic halophilic heterotrophic microbial consortia to introduce Mg replacement on CaCO3 precursors in a timely manner that is comparable to primary precipitation in microbial dolomite experiments. The inability of the enriched microbial consortia to mediate replacement can be ascribed to different factors controlling the diagenetic process compared to primary precipitation in microbial dolomite experiments